EFEK KRIM EKSTRAK BLUBERI (Vaccinium virgatum) TERHADAP ERITEMA PADA KULIT TIKUS WISTAR (Rattus norvegicus) JANTAN YANG DIPAPAR ULTRAVIOLET B AKUT - Ariadi, Pande Putu Yusas; Arijana, I Gusti Kamasan Nyoman; Wahyuniari, Ida Ayu Ika; Linawati, Ni Made (Essence of Scientific Medical Journal; Vol 22 No 2 (2025): Volume 22 No. 2 (November 2024 - Maret 2025) Essential: Essence of Scientific Medical JournalDO - 10.24843/essential.v22i2.121236, 2025)
Introduction: Early damage from UVB exposure results from oxidative stress-mediated erythema. Antioxidants are known for their inhibitory effects on oxidative stress. Blueberries are a natural source of antioxidants. The phenolic components in blueberries can inhibit cancer cell proliferation, reduce macromolecule oxidation, decrease oxidative stress, and regulate inflammation-related cytokine genes. Method: This research used a posttest-only control group design. Sixteen Wistar rats were grouped into four groups, namely the basic cream group (P1), the 4% blueberry extract cream group (P2), the 8% blueberry extract cream group (P3), and the 12% blueberry extract cream group (P4). Erythema was induced by giving UVB radiation 2000 mJ/cm 2 for 8 minutes after applying the cream on the rat's back. Furthermore, erythema was observed and scored after 24 hours. Result: This study showed that there was a significant difference in the erythema score of the group of rats given blueberry extract cream with the group of rats given basic cream (p = 0.04). Groups P2 and P4 showed no decrease in erythema score. Meanwhile, Group P3 showed lower erythema than the control group (P1) (p<0.05). Discussion: Blueberries contain flavonoid active ingredients. Flavonoids are potent antioxidants, which have photoprotective activity. In addition, antioxidants in blueberries have the effect of reducing inflammation and oxidative stress by downregulating the NF-KB pathway and reducing ROS and lipid peroxidation. Conclusion: It is concluded that there is an effect of 8% blueberry extract cream on reducing the erythema score of Wistar rat skin exposed to acute UVB radiation.